KURSI ESTETIS SEBAGAI UNSUR PENGUAT CITRA PADA INTERIOR RUMAH SAKIT - Siti Badriyah (Pendhapa, 2018)
ABSTRAKThe design of the chair can be an alternative aesthetic enrichment for the visual appearance of a hospital . Many hospitals concerned in presenting the image and quality of service for the community even though the level kabupaten.Usaha complementary infrastructure , health care , medical needs and the interior architecture is also increasingly encouraged hospitals to meet the demands of society . Innovation in packaging designers help the image you want presented . Public awareness to use the services of interior designers began to increase in line with the demands of people's lifestyle is in line with industry asesories furniture and architecture , people are not enough to design the interior of the house or his hotel is not professional , but began to trust the experts . Departing from the above phenomena seat design aesthetic to the hospital is an answer to the demand for image performance wise a hospital . The design uses a systematic design method of imagination to reality through several processes namely : searching , planning , inventing and constructing . Chair design aesthetic even this is a process that starts from imagination to become reality design that is able to answer the demands of time for the service and comfort of a wellness center for the community .Â Keywords : aesthetic seats , interior lobby hospital